Application of a Novel AC-DC-AC Converter in Double-fed Adjustable Speed System - ZHANG Xingqi; REN Kaichun; ZHANG Xiaochun (Kongzhi Yu Xinxi Jishu)
By researching on principle of double-fed adjustable speed system based on traditional thyristor AC-DC-AC converter, a novel AC-DC-AC converter topology is proposed. The working principle and main component parameters designing of the new converter are researched. The AC-DC-AC converter and the double-fed adjustable speed system based on the new converter model are established in Simulink of Matlab. The working course of new converter and the typical working conditions of double-fed induction motor are simulated. The results show that the new converter can meet the system’s requirements, and the double-fed induction motor can work in four-quadrant.